Bridging Teacher–Student Perspectives for Differentiated Ethno-STEM Physics Instruction on Climate Change - Rosdiana, Rosdiana; Sriyanti, Ida; Ismet, Ismet; Akhsan, Hamdi Akhsan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Climate change education requires physics instruction that connects scientific concepts with learners’ local experiences while accommodating diverse learning needs. However, differentiated instructional resources that integrate local ecological knowledge remain limited, particularly in South Sumatra. This study investigated teacher and student needs to inform the development of differentiated Ethno-STEM physics instructional materials for climate change learning. A quantitative descriptive needs analysis was conducted involving 988 senior high school students and 68 physics teachers from 13 districts and municipalities in South Sumatra. Data were collected through structured questionnaires and analyzed using descriptive statistics. The findings revealed a strong demand for multimodal process differentiation, with teachers emphasizing the need for structured visual, auditory, and kinesthetic learning pathways, while students showed the strongest preference for experiential learning activities. The analysis also identified notable discrepancies between teachers’ perceptions of the instructional relevance of local wisdom and students’ familiarity with these cultural practices. Teachers further reported challenges related to instructional time, technical guidance, and variations in student readiness. These findings highlight the need for instructional materials that combine multimodal differentiation with culturally meaningful learning experiences. The study provides an empirical foundation for designing differentiated Ethno-STEM physics resources that better align classroom instruction with learner diversity, local ecological contexts, and climate change education.